Childhood factors associated with asthma remission after 30 year follow up. Issue 11 (29th October 2004) - Vonk, J M; Postma, D S; Boezen, H M; Grol, M H; Schouten, J P; Koëter, G H; Gerritsen, J
Abstract : Background: Factors contributing to either "complete" or "clinical" remission of asthma are important to know since there is no cure for the disease. Methods: A cohort of 119 allergic asthmatic children was examined three times with a mean follow up of 30 years. They were aged 5–14 years at visit 1 (1966–9), 21–33 years at visit 2 (1983–6), and 32–42 years at visit 3 (1995–6). Complete remission of asthma at visit 3 was defined as no asthma symptoms, no use of inhaled corticosteroids, normal lung function (FEV1 >90% predicted), and no bronchial hyperresponsiveness (PC10 >16 mg/ml). Clinical remission was defined as no asthma symptoms and no use of inhaled corticosteroids. Results: 22% of the group was in complete remission of asthma at visit 3 and a further 30% was in clinical remission (total 52%); 57% of subjects in clinical remission had bronchial hyperresponsiveness and/or a low lung function. Logistic regression analyses showed that a higher FEV1 in childhood and more improvement in FEV1 from age 5–14 to 21–33 were associated with both complete and clinical asthma remission at age 32–42. Conclusions: Complete remission of asthma was present in a small subset of asthmatics while half the subjects showed clinical remission. Both complete and clinical remission were associated with a higher lung function level in childhood and a higher subsequent increase in FEV1 . These results support the view that defining remission only on the basis of symptoms and medication use will overlook subjects with subclinical active disease and possibly associated airway remodelling.